2021
DOI: 10.5194/esd-12-1295-2021
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the coupled ocean and atmosphere system with a data science approach applied to observations from the Antarctic Circumnavigation Expedition

Abstract: Abstract. The Southern Ocean is a critical component of Earth's climate system, but its remoteness makes it challenging to develop a holistic understanding of its processes from the small scale to the large scale. As a result, our knowledge of this vast region remains largely incomplete. The Antarctic Circumnavigation Expedition (ACE, austral summer 2016/2017) surveyed a large number of variables describing the state of the ocean and the atmosphere, the freshwater cycle, atmospheric chemistry, and ocean biogeo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 197 publications
(237 reference statements)
0
26
0
Order By: Relevance
“…Validation of sizing accuracy of both instruments was performed using polystyrene latex spheres. To minimize influences of the ship exhaust, data filtering was performed for the SMPS and APS data, based on sudden changes in the total aerosol particle number concentration, concentrations of carbon dioxide, black carbon, and wind direction (Moallemi et al, 2021).…”
Section: Aerosol Size Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Validation of sizing accuracy of both instruments was performed using polystyrene latex spheres. To minimize influences of the ship exhaust, data filtering was performed for the SMPS and APS data, based on sudden changes in the total aerosol particle number concentration, concentrations of carbon dioxide, black carbon, and wind direction (Moallemi et al, 2021).…”
Section: Aerosol Size Distributionmentioning
confidence: 99%
“…The combination of both outputs enables interpolation of the gap between the SMPS (D p ≤ 400 nm) and APS (D p > 500 nm) instruments. Further, a mode fitting technique analogue to Modini et al (2015) was applied that is based on a method described in Khlystov et al (2004) and fully described in the supplement to Landwehr et al (2021). In this approach, each PNSD is assumed to be a superposition of up to three aerosol modes, and log-normal distributions in pre-defined size ranges are fitted.…”
Section: Aerosol Size Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…McCluskey et al (2018) found contributions to INP from heat-labile organic substances, indicating a biological source. Generally, INP concentrations appear higher near land compared to over open ocean (Landwehr et al, 2021). The importance of accurate INP concentration for simulating Southern Ocean mixed phase clouds has been demonstrated in a modeling study (Vergara-Temprado et al, 2018), where overly high concentrations led to overly strong precipitation and overly short cloud lifetime.…”
Section: The Important Role Of the Southern Ocean For Atmospheric Chemistrymentioning
confidence: 99%
“…Further questions are related to sea spray, as models tend to over predict sea spray concentrations (Revell et al, 2019;Alroe et al, 2020;Hartery et al, 2020). While more effort has been made to improve the sea spray emission source function, the importance of air mass exchange and deposition processes have received less attention (Landwehr et al, 2021).…”
Section: The Important Role Of the Southern Ocean For Atmospheric Chemistrymentioning
confidence: 99%